Africa's new oil : power, pipelines and future fortunes - Hicks, Celeste; International African institute; Royal African Society; World Peace Foundation (London, UK : Zed Books, 2015)
In recent years, technological advances, higher commodity prices and a global thirst for energy have meant that African oil and gas are inc reasingly in demand. Countries as far apart as Niger, Uganda, Chad, Gha na, Kenya and Tanzania are looking at the prospect of almost unimaginab le flows of money into their national budgets. But the story of African oil has usually been associated with disaster - older producers such a s Nigeria, Angola and Cameroon have little to show for the many billion s of dollars they've earned, and oil money has been shown to fuel confl ict and corruption, creating a so-called 'resource curse'. In this reve aling and insightful book, former BBC correspondent Celeste Hicks quest ions the inevitability of such an outcome, revealing what the discovery of oil means for the ordinary Africans through original testimony from those working in the oil industries and the communities that surround them. A much-needed account of an issue that will likely transform the fortunes of a number of African countries - for better or for worse--
Chad : a model project -- The aftermath -- Lessons learned for China ? -- Resource nationalism in Niger -- Civil society power in Ghana -- T he East Africa miracle? -- Conclusion.
"In association with International African Institute, Royal African Society, World Peace Foundation."
Includes bibliographical references (pages 216-225) and index.
Keywords: Petroleum industry and trade -- Economic aspects -- Africa; Petroleum industry and trade -- Africa